Characterization and Recovery of Minced fish Wastewater Protein using Reverse Osmosis - . Uju; Tati Nurhayati; Bustami Ibrahim; Wini Trilaksani; Maglory Siburian (Jurnal Pengolahan Hasil Perikanan Indonesia, 2009)
Recovery of minced fish wastewater soluble protein was done by reverse osmosis membrane. Themincefish wastewater has high level polluting load. It contains COD and TSS 4.233 and 55,06 mg/lrespectively, but it is potential to utilized because of high protein and amino acids content especiallyglutamic acid. Fluxes of permeate during recovery process were kept on steady state in the beginningprocess at 15 l/m2h without prefiltration and 20 l/m2h with 0,9 micron prefiltration. During concentration,flux time decreased from 22,11 l/m2h at concentration factor 1 to 12,95 l/m2h at concentration factor 1,52.In other sides the rejection value of protein increased from 90,11% in the beginning process to 99,50% inthe end of the concentration process. At the end of the recovery stage, yield concentrate contained 0.401 g/lwhich is 21 fold greater than the original step. Therefore permeate stream delivered high quality effluentand met the standard of wastewater effluent.Keywords: minced fish, protein, recovery, reverse osmosis